2006
DOI: 10.1007/s10722-004-6108-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Ethiopian Mustard (Brassica carinata A. Braun) Germplasm in Western Canada

Abstract: Information on genetic diversity and genetic relationships among genotypes of Brassica carinata is currently limited. The objectives of this study were to evaluate patterns and levels of genetic diversity in B. carinata based on amplified fragment length polymorphisms (AFLP) as compared with Brassica juncea and Brassica nigra, and to evaluate agronomic and seed quality data for plants grown in the field in western Canada. A total of 296 AFLP bands were generated from four primer pair combinations and scored fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
77
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 39 publications
8
77
2
1
Order By: Relevance
“…The separation of genotypes based on PC1 and PC2 revealed that the populations were distributed in all the directions, which clearly recognized the diversification in indigenous landraces of B. napus L. Previous data based on first and second five PCs with > 1 contributed 73.30% and 64.45% of the genetic variability, respectively among various accessions of B. juncea L. (Ali et al, 2015). Past researchers have made divergence studies of morphological and seed attributes using principal component and cluster analyses in Brassica species (Takahata and Hinata, 1986), B. napus L. (Bus et al, 2011;Gyawali et al, 2013), Indian mustard (Dias et al, 1993;Rabbani et al, 1998b), Ethiopian mustard (Alemayehu and Becker, 2002;Genet et al, 2005;Warwick et al, 2006), and white head cabbage (Balkaya et al, 2005). However, the present two methods i.e., cluster and principal component analyses were found more appropriate and can better dig out the relationship between the genotypes of assorted origins.…”
Section: Discussionmentioning
confidence: 99%
“…The separation of genotypes based on PC1 and PC2 revealed that the populations were distributed in all the directions, which clearly recognized the diversification in indigenous landraces of B. napus L. Previous data based on first and second five PCs with > 1 contributed 73.30% and 64.45% of the genetic variability, respectively among various accessions of B. juncea L. (Ali et al, 2015). Past researchers have made divergence studies of morphological and seed attributes using principal component and cluster analyses in Brassica species (Takahata and Hinata, 1986), B. napus L. (Bus et al, 2011;Gyawali et al, 2013), Indian mustard (Dias et al, 1993;Rabbani et al, 1998b), Ethiopian mustard (Alemayehu and Becker, 2002;Genet et al, 2005;Warwick et al, 2006), and white head cabbage (Balkaya et al, 2005). However, the present two methods i.e., cluster and principal component analyses were found more appropriate and can better dig out the relationship between the genotypes of assorted origins.…”
Section: Discussionmentioning
confidence: 99%
“…Mustard (Brassica juncea), a species of the genus Brassica belonging to the family Brassicaceae, is an agriculturally and economically important crop widely cultivated in Asia and Europe (Warwick et al, 2006). All species of mustard are polyploids (AABB), with the chromosome number 2n = 36.…”
Section: Introductionmentioning
confidence: 99%
“…Brassica vegetables contain little fat, and are sources of vitamins, minerals, and fiber. Several species, e.g., Camelina sativa, Crambe abyssinica, Eruca vesicaria, have potential as new edible oil/protein crops, biodiesel fuel crops, or platforms for bioproducts or molecular farming (Warwick et al 2006). The family is also known for its more than 120 weedy species, several of which are important cosmopolitan agricultural weeds (e.g., wild mustard (Sinapis arvensis)), stinkweed (Thlaspi arvense) while others form crop-weed complexes (e.g., Raphanus sativus-Raphanus raphanistrum).…”
Section: Introductionmentioning
confidence: 99%